Efficacy and Safety of Lactobacillus reuteri CCFM1040 in Allergic Rhinitis and Asthma: A Randomized, Placebo-Controlled Trial - Li, Lingzhi; Fang, Zhifeng; Lee, Yuan-kun; Zhao, Jianxin; Zhang, Hao; Peng, Huaiming; Zhang, Yulong; Lu, Wenwei; Chen, Wei (Frontiers in Nutrition, 2022)
The coexistence of allergic rhinitis (AR) and asthma reinforces the concept of “one airway, one disease,” which has prompted the exploration for a single intervention to treat both diseases. Lactobacillus reuteri CCFM1040 (CCFM1040) was found to be an inhibitor of the common pathogenesis of AR and asthma in our previous studies. This study presented a randomized, placebo-controlled trial to investigate the clinical effects of CCFM1040 on both diseases. The total symptom score (TSS), the quality of life (QoL), and the modulation in the gut microbiota of patients with AR, the Asthma Control and Test (ACT) of patients with asthma, and the safety of both AR and asthma were measured. In patients with AR, CCFM1040 numerically decreased TSS, Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ), 3 nasal scores in TSS (nasal congestion, watery eyes, and rhinorrhea), and sleep and significantly improved (P = 0.014) non-nose/eye symptoms. The ACT score was numerically increased in patients with asthma (from partially controlled to well-controlled). Significant microbial (from class level to genus level) and metabolic differences (P < 0.05) were found in patients with AR. No adverse reactions were observed. No effect on the blood and urine routine indexes. CCFM1040 has a potential benefit on both diseases. Further studies based on these findings will help to optimize the management of AR and asthma.